Midsymphyseal distraction osteogenesis: A new alternative for the treatment of dental crowding - Gandini Júnior, Luiz Gonzaga [UNESP]; Martins, Renato Parsekian [UNESP]; de Oliveira, Cristina Azevedo; Abdala, Anamaria; Buschang, Peter H. (Mosby-elsevier, 2009)
In this article, we describe a midsymphyseal distraction osteogenesis treatment with a novel dentally supported appliance. This approach differs from that used in previous reports because the incisors were allowed to move during the distraction procedure. This report shows that midsymphyseal distraction osteogenesis can be used to expand both arches to produce a wider smile. Borderline cases can be treated with this technique without the compromising effects commonly observed with conventional therapy. (Am J Orthod Dentofacial Orthop 2009;135:530-5)